Problem Based LearnÄ±ng Model wÄ±th Blended LearnÄ±ng Approach to The EffectÄ±veness of Student LearnÄ±ng Outcomes - Alfiah Alfiah; Subandowo Subandowo; Sugito Sugito (STAI Syaichona Moh. Cholil Bangkalan, 2022)
The low completion of student learning in a subject is the reality of the quality of education in schools. The model in learning is one of the factors that can cause an impact on students' learning achievements. The use of the learning model must be adjusted to the characteristics of the student himself and the subjects taught.Â This article is intended to reveal the differences in blended-based Problem Based Learning (PBL) learning and Problem Based Learning (PBL) learning to the learning outcomes of students of Class X at SMK Negeri in Bangkalan and describe the influence of interaction between blended-based Problem Based Learning (PBL) learning model and learning motivation for the learning outcomes of students of Class X at SMK Negeri in Bangkalan.. This research used quantitative research with experimental methods. In this case, it used two tools, namely questionnaire survey and learning result test. The experimental classes in this study used the blended-based Problem Based Learning (PBL) model conducted online learning and offline and face-to-face learning, while the control classes used the PBL (Problem Based Learning) model for face-to-face learning. This quantitative research used the data analysis technique through the two-way variant analysis (ANOVA) technique. The results showed that the baseline estimate of student learning outcome using the PBL learning model was 40, the highest score was 90, the average score was 72.33, and the standard deviation was 16,439. Compared to the learning outcome of students who used the problem-based learning (PBL) model the lowest score was 45, the highest score was 95, the average score was 80.67, and the standard deviation was 11,502. Seeing from the results of the exploration, it can be concluded that the results of the blended-based Problem Based Learning model are higher, or in other words, students' learning outcomes become more effective by using the approach.